To Flourish or Languish, that is the question: Exploring the mental health profiles of Danish elite athletes. (January 2021) - Kuettel, Andreas; Pedersen, Andreas K.; Larsen, Carsten H.
Abstract: Objectives: The purpose of this study was (a) to investigate mental well-being and the prevalence of anxiety and depressive symptoms in Danish male and female elite athletes, (b) to identify latent profiles in athletes based on their mental health and ill health, and (c) to examine whether the different profiles vary in selected protective and risk factors concerning mental health. Methods: A total of 612 Danish athletes ( M  = 18.99, SD  = 4.29) from 18 different sports completed an online version of the Holistic Athlete Mental Health Survey that assessed well-being, depression, and anxiety together with potential risk and protective factors (e.g., injuries, stress, sleep, social support, sport environment). Results: Overall, 13.9% of athletes reported moderate or severe anxiety symptoms while 21.1% reported moderate or severe depressive symptoms. Female athletes had a significantly higher prevalence of anxiety and depressive symptoms and lower mental well-being scores than male athletes. Through a latent profile analysis, three distinctive mental health profiles (flourishing, moderate mental health, languishing) were discovered. MANOVA following Kruskal-Wallis tests revealed substantial differences between these profiles regarding their perception of social support, sport environment, and stressors from different life domains. C onclusions: Danish elite athletes display similar levels of anxiety and depressive symptoms as the Danish general population. Flourishing athletes report lower stress levels, receive higher support from the private and sport domain, and perceive their sport environment as more supportive than athletes who are languishing. A tailored approach is proposed to support athletes' mental health. Highlights: Danish athletes have similar anxiety and depression rates as the Danish population. Female athletes experience lower mental well-being than male athletes. Three distinctive latent mental health profile of athletes were discovered. Two-thirds of athletes are flourishing, receiving high social support in sport/life. A minority of athletes is languishing, expressing high stress and low social support.